Analisis Kerusakan Housing Burner Mesin Boiler Type Watertube Kapasitas 2.500 Kg/Jam Di PT. Pratapa Nirmala - Abdul Choliq; septian ari priyanto (Politeknik Negeri Semarang, 2026)
This research focuses on the failure analysis of the housing burner component in a watertube-type boiler with a capacity of 2,500 kg/hour, operated at PT Pratapa Nirmala Pharmaceutical Industry. This study aims to analyze the failure of a housing burner component in a watertube boiler with a capacity of 2,500 kg/h used in the pharmaceutical industry at PT Pratapa Nirmala. Post-operation inspection revealed significant material erosion on one side of the housing burner in the combustion chamber area, which may reduce combustion efficiency and adversely affect the overall boiler performance. To identify the failure mechanisms and root causes, material analyses were conducted on several sample conditions, including worn, non worn, raw material, and heat-treated samples. The investigation involved microstructural observation using optical microscopy and surface morphology analysis using Scanning Electron Microscopy (SEM) to evaluate the extent of surface degradation, the presence of microcracks, oxidation, and porosity. The results indicate that the material degradation is progressive and non-uniform, suggesting an imbalance in heat distribution and combustion gas flow, which is likely associated with misalignment during housing burner installation. Heat treatment was evaluated to assess its potential in improving wear resistance and thermal stability of the material, serving as a basis for technical recommendations regarding design improvement, installation methods, and maintenance strategies for the housing burner.